State Responsibility for Environmental Damage from Climate Change under the No-Harm Principle - Dewanto, Wisnu Aryo; Krustiyati, J. M. Atik (Fakultas Hukum Universitas Hang Tuah, 2024)
This research delves into the critical role of states in addressing environmental damage stemming from climate change, underpinned by the fundamental principle of “no harm”. Climate change represents a profound threat to both the global ecosystem and human welfare, necessitating concerted action from all nations. The no harm principle places an obligation on states to undertake effective measures to mitigate greenhouse gas emissions, facilitate adaptation to climate change impacts, and mitigate adverse effects on vulnerable communities. This research uses normative legal research methods with a regulatory and contextual approach. By examining both theoretical frameworks and legal instruments, the study aims to elucidate the responsibilities of states and the mechanisms through which they can fulfill these obligations. A central focus of this research is the examination of how nations collaborate internationally to achieve climate change mitigation and adaptation goals through global agreements. These agreements serve as frameworks for collective action, guiding states in their efforts to combat climate change and minimize its harmful effects. By emphasizing the no harm principle, this study seeks to deepen our understanding of state responsibility for climate change and associated environmental damage. It underscores the imperative for robust collaborative endeavors aimed at safeguarding the global environment and ensuring a sustainable future for all. Through enhanced awareness and collective action, states can fulfill their duty to protect the planet and mitigate the adverse impacts of climate change on present and future generations.